I know what you did last summer [videorecording (Blu-Ray)] - Robinson, Jennifer Kaytin; Lansky, Sam; McKendrick, Leah; Cline, Madelyn; Wonders, Chase Sui, 1996-; Hauer-King, Jonah, 1995-; Withers, Tyriq; Pidgeon, Sarah; Campbell, William, 1959-; Gellar, Sarah Michelle, 1977-; Prinze, Freddie, Jr; Hewitt, Jennifer Love, 1979-; et al. (Sony Pictures, 2025)
"When five friends inadvertently cause a deadly car accident, they cover up their involvement and make a pact to keep it a secret rather than face the consequences. One year later, the past comes back to haunt them as they learn someone knows what they did last summer. Stalked by a mysterious killer, they soon seek help from two survivors of the legendary Southport massacre of 1997."--